Synthesis of novel 6-piperidin-1-ylpyrimidine-2, 4-diamine 3-oxide substituted calix[4]arene as a highly selective and sensitive fluorescent sensor for Cu2+ in aqueous samples. Issue 13 (26th March 2020) - Akbarzadeh, Ali; Zadmard, Reza; Jalali, Mohammad Reza
Graphical abstract: Highlights: Novel 6-piperidin-1-ylpyrimidine-2, 4-diamine 3-oxide substituted calix[4]arene. A highly selective and sensitive fluorescent sensor for Cu 2+ . The structure of the target molecule was determined by HRMS, 1 H NMR, 13 C NMR and FT-IR. Abstract: In this study, we designed and synthesized a novel sensitive fluorescent sensor for Cu 2+ cation by attaching two minoxidil molecules at the lower-rim of calix[4]arene annulus via the formation of two urea linkages. This chemosensor can selectively recognize Cu 2+ in EtOH containing 5% H2 O through a significant decline in fluorescence emission. The structure of the target molecule was determined by HRMS, 1 H NMR, 13 C NMR and FT-IR.